C–H bond activation induced by thorium metallacyclopropene complexes: a combined experimental and computational study1. Issue 8 (14th August 2015) - Fang, Bo; Zhang, Lei; Hou, Guohua; Zi, Guofu; Fang, De-Cai; Walter, Marc D.
<x xml:space="preserve">Abstract</x> Thorium metallacyclopropenes derived from phenyl(alkyl)acetylenes are very reactive complexes that undergo selective intramolecular C–H bond activation.